The Role Of Family Social Support In Decision Making Using Long-Term Contraceptive Methods - Sindi Eka Putri; Sri Widati (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2020)
Background: One of the efforts made by the government to reduce the rate of population growth was through the Family Planning program. Many contraceptive methods are used by Fertile Age Couples (FAC), including the Long-Term Contraception Method (MKJP) and the non-Long-Term Contraception Method (non-MKJP). Low interest in fertile-couples for long-term use of contraception cannot be separated from family support to use these contraceptives. There is a need for an understanding of MKJP for FAC. Family support was defined as the attitude, actions, and acceptance of the family of its members. Family members see that those who are supportive are always ready to provide help and assistance. With family support, FAC can easily decide which contraception will be used. Objective: The purpose of this study was to analyze the relationship of family social support to the interest of FAC in using the long-term contraception method in RW 5, Sidotopo Village. Methods: This research was an observational analytic study using a cross-sectional research design. The sample of this research consists of 48 participants, taken randomly using multistage random sampling. The research instrument was in the form of a questionnaire. Then, the data were analyzed using the Chi-square test. Results: The characteristics of family planning acceptors in RW 5 of the Sidotopo sub-district starting from the dominating age are 21-35 years old with high school as the highest level of education. The income level in the area is middle to the upper level from 2 million to 5 million rupiahs per month. Based on the results of statistical tests, there is a correlation between family instrumental social support with the interest of Fertile Age Couples to use MKJP. Conclusion: Based on the results of the bivariate test using Chi-Square, it was found that between the four support variables, only one of them has a relationship that is instrumental support. The results of this study can be used as a rationale for policymaking in order to increase the number of long-term family planning acceptors.